Hukou and Citizenship Rights in China: A Case Study on Migrant Labour - MANGANELLY, SUMESH (Jurnal Dinamika Sosial Budaya, 2019)
Abstract This article is going to discuss hukou in detail and how it juxtaposes with citizenship rights of migrants in China. The first part of this article deals with China s hukou policies and its implications on Chinese society and going to discuss how migrants are trying to fit city life even within this tight and strict hukou system. The second section talks about the denial of the complete citizenship to the floating population in their country, and how they are treated as secondary citizens by urban people. Also, article tries to bring the basic concept of citizenship in the light of the state policies of denial of their rights and discriminating its rural population even though they have been the fuel of Chinese rapid economic and infrastructural growth and made China as world s factory. The third and final part examines the provisions of hukou and juxtaposes them with the notion of citizenship to show how they contradict each other in contemporary China in the era of domestic migration. So, it is a bit difficult situation to clarify those Chinese concepts of legitimising their views with the modern concept of citizenship. Still, it is an attempt to elaborate and conceptualise life and rights of migrants in Chinese cities. Keywords: China, Migrants, hukou, Citizenship rights